Bio-resolução de adutos de Morita-Baylis-Hillman mediada pela enzima Lipase CALB:bioatividade de seus enantiômeros puros - Xavier, Francisco José Seixas (2013)
This work aimed to perform the kinetic bioresolution of Morita Baylis Hillman adducts (MBHA) using CALB lipase derived from Candida Antarctica fungus. Initially three MBHA we synthesized using acrylonitrile and m e p nitro benzaldehyde. Subsequently the respective acetates from MBHA were prepared in high yields using acetyl chloride and TEA. Methodologies for bioresolution of AMBH (obtained from nitro aldehydes m e p) were successfully developed producing the R enantiomers with 99.9% of enantiomeric excess determined by gas chromatography (using the beta cyclodextrin chiral column). However, using the same methodology it was not possible performed the bioresolution of AMBH derived from the o-benzaldehyde. To obtain the S enantiomers, the hydrolysis reactions of esters obtained from biocatalysis were made and separated by liquid chromatography. These hydrolysis reactions were carried out using K2CO3 and methanol, yielding the S enantiomers with 100% and 10% of chemical yields and 86.8% and 97.48% of enantiomeric excesses respectively. Using the method of Mosher through double derivatization chemical shift values obtained from 1H NMR spectra generated a NORS> and NORS 0 <0, which indicates that the absolute configuration of the asymmetric carbon of AMBH hydrolyzed by enzyme is R. The values of [S] D derived from m and p nitro aldehydes (S configuration) are +37 and +30 degrees. The values of [S] D of S corresponding acetates are -7 and -9 degrees respectively. The AMBH obtained from the m nitro aldehyde were bioavaliados in vitro in a R/S, R and S forms. The racemate was the most effective on L. braziliensis promastigotes and the S enantiomer was the lowest active. In the cell cytotoxicity analysis which were evaluated in the safe murine macrophages, the racemate was the most cytotoxic and the S enantiomer the less cytotoxic (some cytotoxicity were only observed at concentrations over 40 mg/mL) concluding that all evaluated compounds were more cytotoxic for L. braziliensis parasite that the safe macrophage.